2019
DOI: 10.7759/cureus.4603
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Novel Food Supplement (Ferfer®) Containing Microencapsulated Iron in Liposomal Form in Female Iron Deficiency Anemia

Abstract: Introduction Iron deficiency anemia (IDA) is a highly afflicting condition which affects young children of growing age and reproductive age women in countries of lower economies. Conventional oral iron salts have poor absorption and gastrointestinal side effects. Microencapsulated liposomal iron pyrophosphate is a novel compound with enhanced palatability, higher bioavailability, and consequently increased adherence among people with IDA. This study aims to assess the efficacy of microencapsulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 11 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…To date, several applications of micronized and microencapsulated iron in the management of ID and IDA have been described, however, mostly as food fortification approaches in children as well as in adults [ 22 , 23 , 24 , 25 , 26 , 27 ]. Only recently, the results of studies on micronized, microencapsulated iron as stand-alone food supplements in the form of a powder [ 28 ], an oro-dispersible stick [ 29 ], or a tablet [ 30 ] in a population of generally healthy women with or without ID have been published. To our knowledge, the present study is the first one to report on the usefulness of micronized and microencapsulated iron as a stand-alone liquid food supplement in providing nutritional support in an ID pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several applications of micronized and microencapsulated iron in the management of ID and IDA have been described, however, mostly as food fortification approaches in children as well as in adults [ 22 , 23 , 24 , 25 , 26 , 27 ]. Only recently, the results of studies on micronized, microencapsulated iron as stand-alone food supplements in the form of a powder [ 28 ], an oro-dispersible stick [ 29 ], or a tablet [ 30 ] in a population of generally healthy women with or without ID have been published. To our knowledge, the present study is the first one to report on the usefulness of micronized and microencapsulated iron as a stand-alone liquid food supplement in providing nutritional support in an ID pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the hemoglobin levels in those women significantly increased from 8.71 ± 2.24 to 10.47 ± 1.69. 145 In a more recent study, de Alvarenga Antunes et al designed a study on patients who had inactive or mildly active inflammatory bowel disease (IBD) and IDA. The patients took oral liposomal iron for 8 weeks.…”
Section: Recent Studies On Improving Iron Bioavailabilitymentioning
confidence: 99%
“…Therefore, it might be expected that, via the transient iron loading of erythrophagocytosing RPMs and KCs, such drugs may cause the depletion of these cells and hence trigger some degree of iron-recycling niche remodeling. Novel and promising formulations for oral iron delivery that are based on liposomal encapsulation [ 140 ] still need to be investigated in more detail for their biodistribution among different cell types.…”
Section: Development and Plasticity Of Iron-recycling Macrophagesmentioning
confidence: 99%